The Arabic manuscript tradition : a glossary of technical terms and bibliography - Gacek, Adam (Handbuch der Orientalistik. Nahe und der Mittlere Osten, 2001)
Covering the entire spectrum of Arabic manuscripts, and especially the handwritten book, this book consists of a glossary of technical terms and a bibliography. The technical terms, collected from a variety of sources, embrace a vast range of topics dealing with the studying of Arabic manuscripts.